Systematic Literature Review : A Study of Translanguaging Employed by Yunior High School in Indonesia - Ade Masroni; Nafan Tarihoran (International Journal of Multilingual Education and Applied Linguistics, 2026)
This systematic literature review examines the implementation of Content and Language Integrated Learning (CLIL) in Indonesian senior high schools. Following PRISMA guidelines, nine studies published between 2021 and 2025 were analyzed to identify the benefits and challenges of this approach. The findings reveal that CLIL effectively enhances student engagement, motivation, and the integrated development of subject knowledge and English proficiency. However, implementation is often hindered by limited teacher readiness, insufficient collaboration between subject and language teachers, and a lack of appropriate assessment methods. Analysis using the 4Cs Framework shows that while Content and Communication are prioritized, Cognition and Culture receive less explicit attention. The study implies that successful CLIL sustainability requires continuous professional development and stronger institutional support within the Merdeka Curriculum. These results provide a strategic basis for educators and policymakers to optimize bilingual instruction in Indonesia.